FACTORS AFFECTING IMPULSIVE BUYING IN MOBILE COMMERCE WITH STIMULUS-ORGANISM-RESPONSE (S-O-R) PERSPECTIVE - Kartika Sari; Dwinita Laksmidewi (Journal of Business Studies and Management Review, 2021)
This research aims to learn the factors that impact impulse buying in online purchases using mobile commerce with a stimulus-organism-response (SOR) perspective in the e-commerce industry. Data collection using online surveys with sampling using purposive sampling, only buyers who have done online shopping using smartphones on e-commerce platforms. Data processing using Partial Lease Square-Structural Equation Model (PLS-SEM). The research analysis outcomes that the architectural quality of the website, promotion campaign, and enjoyment have a significant effect on positive affect. Furthermore, positive affect has a positive and significant effect on impulsive buying. Positive affect has a complementary mediation effect in the correlation between the architectural quality of the website and enjoyment of impulsive buying. Meanwhile, positive affect becomes a competitive mediation in the correlation between promotion campaigns and impulsive buying. Keywords: Architectural quality of website, promotion, enjoyment, positive qffect, impulsive buying, Stimulus-Organism-Response (S-O-R), mobile commerce